A seed-mediated approach to the general and mild synthesis of non-noble metal nanoparticles stabilized by a metal–organic framework for highly efficient catalysis. Issue 6 (6th August 2015) - Chen, Yu-Zhen; Liang, Linfeng; Yang, Qihao; Hong, Maochun; Xu, Qiang; Yu, Shu-Hong; Jiang, Hai-Long
Abstract : A novel noble metal-seed-mediated approach to reduce non-noble metals under mild conditions to afford non-noble metal NPs with superior catalytic performance. Abstract : A novel and facile in situ seed-mediated synthetic approach has been developed to reduce non-noble metal precursors (Ni 2+, Co 2+, Fe 2+, etc. ) at room temperature, by taking advantage of a trace amount of noble metal cations (Ag +, Pd 2+, Pt 2+, Au 3+, etc. ) as a seed/initiator and NH3 BH3 as a moderate reducing agent. The obtained noble metal-seed-mediated (NMSM) non-noble metal nanoparticles (NPs), stabilized by a metal–organic framework, are low-cost and display superior catalytic activity in the hydrolytic dehydrogenation of NH3 BH3 under ambient conditions. As a representative catalyst, Ag-doped Ni/MIL-101 (with a Ag/Ni molar ratio as low as 1/200), exhibited a much higher activity than any of the other corresponding counterparts.